Detecting the presence of red heart in beech (Fagus sylvatica) using electrical voltage and resistance measurements - Göncz Balázs (EUROPEAN JOURNAL OF WOOD AND WOOD PRODUCTS, 2017)
Red heart is one of the most important visual defects in beech wood. Its detection is difficult, since its mechanical characteristics do not differ significantly from sound wood. However, its electric conductivity is different, which offers an opportunity for detecting beech red heart. Initial measurements using a 24-channel impedance tomograph were very efficient in detecting red heart due to its significantly lower electric resistance. High conductivity regions on the resistance map corresponded to the size and shape of the red heart. An 8-detector setup was investigated in a laboratory setting to establish the best electrode arrangement to develop a simple and reliable on-site detection method. On-site measurements, using only four electrodes, proved to be highly reliable to detect the presence of red heart in beech trees of 40–60 cm diameter. In the meantime, the method did not seem capable of determining the extent of red heart. The diameter of the tree was found to have very little effect on the measured voltage. Therefore, there is no need for diameter-correction in the examined diameter range.